Advanced Data Visualizations: 10 Uncommon Plot Types and How to Use Them. - Buscha, Franz (linkedin.com, 2023)
Learn about 10 types of graphs that you might not encounter in regular practice, why these advanced graphs are needed, and what their advantages and disadvantages are.